Experimental investigation on heat transfer with a Phase Change Dispersion. (25th January 2019) - Fischer, Ludger; Maranda, Simon; Stamatiou, Anastasia; von Arx, Silvan; Worlitschek, Jörg
Highlights: Phase Change Dispersions (PCD) have a high potential to be used as cooling fluid due to their enlarged heat capacity. Apparatus is presented to measure convective heat transfer coefficients of a PCD flowing through a circular tube. Experimental results presented with a PCD that consists of dispersed paraffin in water. Abstract: A Phase Change Dispersion (PCD) consists of a carrier fluid and a dispersed Phase Change Material (PCM) that changes from solid to liquid while absorbing heat at nearly constant temperature. Due to the phase change of the PCM, the PCD is an efficient heat transfer fluid that enables storing latent heat. To use PCD in technical applications, comprehensive understanding of the heat transfer mechanism is required. A test rig to measure bulk fluid and inner wall temperatures of a PCD flowing through a tube under constant heat flux boundary condition is presented. The temperature measurements allow to calculate local heat transfer coefficients and the apparent specific heat capacity of the PCD. Tests with water were performed and verified with known correlations. Results of experiments with PCD that consists of dispersed paraffin in water are presented and discussed for Reynolds number between 3500 and 5500. It was observed that the apparent heat capacity, what correlates with the amount of heat that was absorbed through the phase change of the paraffin particles, had a remarkable influence on the heat transfer characteristic. The higher the apparent heat capacity, the larger was the heat transfer coefficient. The comparison of the performed experiments showed that the temperature increase of the PCD was approximately 42% less compared to water at same mass flow. For the case of equal Reynolds number, the PCD experiment showed larger heat transfer coefficient compared to water.